How do idiosyncratic deals influence innovation performance? From the perspective of coworker - Ding, Chen; Deng, Lingxiao; Yang, Jing; Chai, Jiayun (Frontiers in Psychology, 2022)
In the hypercompetitive marketplace, contemporary organizations incorporate the diversity of talents into job design (i.e., offering idiosyncratic ideals), in order to meet the unique needs of talented employees and achieve the purpose of attracting, motivating, and retaining them. Based on the cognitive-affective processing system framework, this study aims to explore the effect of coworkers’ perceptions of employees’ idiosyncratic deals (CPEID) on coworker innovation performance, the mediating role of thriving at work, and the moderating role of humility. Two-wave data were obtained from 248 employees of 15 China firms. The findings suggest that (a) CPEID increase coworker innovation performance by fostering coworker learning; (b) CPEID decrease coworker innovation performance by undermining coworker vitality; (c) Coworker humility not only positively moderates the relationship between CPEID and coworker learning, but also positively moderates the indirect effect of coworker learning between CPEID and coworker innovation performance; and (d) the moderating role of coworker humility is not significant in the relationship between CPEID and coworker vitality. This study provides a theoretical explanation for whether CPEID have both positive and negative effects on coworker innovation performance and extends boundary conditions of i-deals. Besides, the findings inspire managers to make reasonable use of the positive role of i-deals.